Dosimetric characterization of 192Ir source-Leipzig applicators sets for surface cancer treatment with Monte Carlo code MCNP4C - Pedraza., R.; Rojas., E. L.; Mitsoura., E. (Revista Mexicana de Ingenieria Biomedica, 2009)
Monte Carlo simulations were done to characterize a radioactive Nucletron Classic Ir source with Leipzig applicators (3 for the horizontal loading position and 3 for the vertical loading position) used in clinical treatments to irradiate superficial cancerous or non-cancerous lesions. The dosimetric characterization was made for each source applicator system using the MCNP4C2 code. The percentage depth dose (PDD), the maximum dose rate and the dose profiles expressed as a percentage with respect to the maximum dose and the dose distribution curves were obtained. The maximum dose rate values absorbed in water for a 370 GBq source are: 4.53 cGy/s +- 0.1268, 4.46 cGy/s +- 0.0783, 4.49 cGy/s +- 0.1268 for the 1, 2 and 3 cm diameter applicators and the source with a horizontal position respectively. When the source is in a vertical position, the following was obtained: 2.70 cGy/s +- 0.0393, 2.68 cGy/s +- 0.1226 and 2.65 cGy/s 0.1171 for 1, 2 and 3 cm aperture respectively. Characterized the 6 source-applicator systems in the longitudinal, transverse and radial axes, the 100%, 95%, 90%, 80%, 70%, 60%, 50%, 40% and 30% dose distribution curves were built. These distributions were normalized at 0.05 cm depth along the central axis of the applicator. Our surface dose rate values have a maximum relative difference of 2.24% with those of Evans for the horizontal applicator with 3 cm in aperture (experimentally obtained) and 0.67% with those of Leon (calculated by MC). The PDD values obtained are statistically the same as those of Evans on the surface but differ by 0.28 % at the depth of 2 mm, 2.46 % at 5 mm and 5.2 % at 10 mm. The surface dose profiles coincide with those of Leon and Evans a differ by 0.53% at 4 mm depth as a maximum. Source position is critical since the maximum dose rate values differ considerably between the horizontal source position and the vertical source position, for the same applicator aperture. However, the dose distribution at depths smaller than 2 mm in both cases are similar, showing a maximum difference of 1.5%.